THERMOPLASTIC RESIN COMPOSITION - NAGATA KOSUKE; TSUNODA ATSUSHI (2021)
To provide a thermoplastic resin composition which is excellent in heat resistance and impact resistance characteristics and suppresses resin deterioration during molding retention and under a high-temperature and high-humidity environment.SOLUTION: The thermoplastic resin composition contains, based on 100 pts.wt. of a resin component comprising (A) 1-99 pts.wt. of a polycarbonate resin (component A) and (B) 99-1 pt.wt. of a polyarylate resin (component B), (C) 0.001-2 pts.wt. of a phosphate-based compound (component C), (D) 0.001-2 pts.wt. of a phenolic compound (component D), and (E) 1-15 pts.wt. of a rubbery polymer (component E).SELECTED DRAWING: None 【課題】耐熱性、耐衝撃特性に優れ、成形滞留時および高温高湿環境下での樹脂劣化が抑制される熱可塑性樹脂組成物を提供する。【解決手段】（Ａ）ポリカーボネート樹脂（Ａ成分）１〜９９重量部および（Ｂ）ポリアリレート樹脂（Ｂ成分）９９〜１重量部からなる樹脂成分１００重量部に対し、（Ｃ）リン酸エステル系化合物（Ｃ成分）０．００１〜２重量部、（Ｄ）フェノール系化合物（Ｄ成分）０．００１〜２重量部並びに（Ｅ）ゴム質重合体（Ｅ成分）１〜１５重量部を含有することを特徴とする熱可塑性樹脂組成物。【選択図】 なし